STUDI KOMPARASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DAN THINK PAIR SQUARE (TPS) TERHADAP PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 1 UJUNGBATU - Dita Amelia; Johni Azmi; Jimmi Copriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aimed to find out student’s achievement the better one between cooperative learning models types Numbered Head Together (NHT) and Think Pair Square (TPS) on learning topic of Coloid by comparing these two models. This is a quasi experimental research with pretest-posttest design. Population on this research are all classes of science in SMA Negeri 1 Ujungbatu consisting of five classes. The subject of this research are XI IPA 4 as the experimental class of TPS and XI IPA 5 as the experimental class of NHT, which were determined randomly after conducting normality and homogeneity test. The data analysis to test the hypothesis was using two tail t-test. Based on the data analysis, it is obtained that tcount = -0,0926 and-ttable = 2,00 with α = 0,05, dk = 62. tcount lies between –ttable and ttable is -2,00≤-0,926≥2,00. H0 accepted, it means there are no significant differences between the student’s achievement by using cooperative learning model type Numbered Head Together (NHT) and the student’s achievement by using cooperative learning model type Think Pair Square (TPS) on the learning topic of Coloid in SMA Negeri 1 Ujungbatu.Keywords: NHT, TPS, learning achievement, Coloid